2013
DOI: 10.1042/an20130015
|View full text |Cite|
|
Sign up to set email alerts
|

Drug-Primed Reinstatement of Cocaine Seeking in Mice: Increased Excitability of Medium-Sized Spiny Neurons in the Nucleus Accumbens

Abstract: To examine the mechanisms of drug relapse, we first established a model for cocaine IVSA (intravenous self-administration) in mice, and subsequently examined electrophysiological alterations of MSNs (medium-sized spiny neurons) in the NAc (nucleus accumbens) before and after acute application of cocaine in slices. Three groups were included: master mice trained by AL (active lever) pressings followed by IV (intravenous) cocaine delivery, yoked mice that received passive IV cocaine administration initiated by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 61 publications
3
18
2
Order By: Relevance
“…In these experiments, we used a modified internal pipette solution and two different holding potentials to monitor sEPSCs and sIPSCs in the same neuron (Ma et al, 2013). As compared with air controls, CIE-treated mice showed increases in the amplitude (one-way ANOVA: F (3, 39) = 2.889, p = 0.0476; Figure 4a), but not frequency (Figure 4b) of spontaneous excitatory synaptic currents (measured as inward currents at − 70 mV).…”
Section: Wd From Cie Alters Spontaneous Synaptic Transmission Of Lofcmentioning
confidence: 99%
See 1 more Smart Citation
“…In these experiments, we used a modified internal pipette solution and two different holding potentials to monitor sEPSCs and sIPSCs in the same neuron (Ma et al, 2013). As compared with air controls, CIE-treated mice showed increases in the amplitude (one-way ANOVA: F (3, 39) = 2.889, p = 0.0476; Figure 4a), but not frequency (Figure 4b) of spontaneous excitatory synaptic currents (measured as inward currents at − 70 mV).…”
Section: Wd From Cie Alters Spontaneous Synaptic Transmission Of Lofcmentioning
confidence: 99%
“…Amplitude (pA) and area (pA/ms) of synaptic events were measured to determine the effects of WD from CIE on evoked AMPA and NMDA EPSCs. In separate set of experiments, a cesium methanesulfonate internal pipette solution (in mM: 125 CsMeSO 3 , 10 CsCl, 5 NaCl, 10 HEPES, 1 EGTA, 2 MgCl 2 , 5 MgATP, 0.3 NaGTP) was used to measure spontaneous EPSCs (sEPSCs) and inhibitory postsynaptic currents (IPSCs) in the same neuron by recording events at a membrane potential at − 70 or 10 mV, respectively (Ma et al, 2013). Spontaneous events were detected using a template matching algorithm and a threshold amplitude of 6 pA for sEPSCs and 10 pA for spontaneous IPSCs (sIPSCs).…”
Section: Evoked and Spontaneous Synaptic Currentsmentioning
confidence: 99%
“…Therefore, we used DiOlistic labeling to explore alterations in dendritic arborization and spine morphology of MSNs in the NAcc of HIV-1 Tg female rats. The MSNs in the NAcc represent an important component of the motivational/reward system mediating substance abuse (Ma et al 2013), which is often co-morbid with HAND in women (Meyer et al 2013; Maki and Martin-Thormeyer 2009). Thus, identification of altered MSN synaptodendritic structures in HIV-1 Tg female animals is a key step in clarifying possible neuropathological substrates of HAND.…”
mentioning
confidence: 99%
“…Thus, natural or psychostimulant conditioned rewarding stimuli can activate MSN neuronal populations recorded in rodents during behavioral reinforcement paradigms (Lansink et al, 2010;Ma et al, 2013). Indeed, Taha and Fields (2005) reported that a plurality of identified MSNs showed excitatory responses associated with sucrose reward exposure in rats.…”
Section: Discussionmentioning
confidence: 99%